A small, stainless-steel sieve optimized for laboratory beaker-based extraction of microplastics from environmental samples - Ryota Nakajima (MethodsX, 2019)
Removing non-plastic materials is a mandatory process for studying microplastics in environmental samples, and non-plastic materials, both inorganic and organic matter, are often removed chemically through sequential processes. In the multiple chemical treatment processes, the samples need to be collected and the reagent removed at the end of each chemical treatment before the samples are again exposed to a different reagent in a separate container. This leads to a loss of microplastics to some extent. Here, we developed a new, yet simple, small sieve made of stainless-steel that can fit in a laboratory beaker (e.g. 200 ml volume), allowing it to be transferred as-is between chemical treatments of environmental samples, even being soakable in a beaker of acid solution. The collection rates of microplastics were significantly higher in the small stainless-steel sieve than the commonly used filter method for different size of microplastic particles. The use of the new sieve means the processes of rinsing off and filtering samples can be abbreviated throughout the entire process of non-plastic matter removal from environmental samples, contributing to a lower chance of microplastic loss. The time consumed in the sieve method was also significantly lower than for the filtering method due to the elimination of the collection and rinsing steps, thus the use of this sieve can reduce processing time for the samples. The new method is innovative in terms of reducing both the microplastic loss and processing time during chemical treatment processes. • The method developed allows the lower chance of microplastic loss during chemical digestion process • The method reduces the time of sequential processes during chemical digestion Method name: Small stainless-steel sieve, Keywords: Sample preparation, Time consuming, Underestimation, Non-plastic matter removal